TINJAUAN HAK ASASI MANUSIA TERHADAP KASUS PEMENJARAAN PENOLAK DINAS MILITER KOREA SELATAN (STUDI PRESKRIPSI PERAN KOMITE HAK ASASI MANUSIA PERSERIKATAN BANGSA-BANGSA) - Myra Karlini Bujung; Anugrah Adiastuti (Faculty of Law Universitas Sebelas Maret, 2017)
The main issue in this research is about injustice situation occur in South Korea regarding to the Conscientious Objection to Military Service. In the past 6 decades, sincere young men in South Korea have been convicted because of their refusal to the Miltary Service for reason of conscientious and their religion belief. Up until now, over 19.000 have been sentenced to imprisonment, which Jehovah’s Witnesses in majority. In 2007, the Korean Government announced that it would introduced an alternative service system for conscientious objectors. However in the following year, it canceled the plan because majority of people did not supported. This Korean Government stand on this issue draws international attention. In 2007, 2010, 2011, and in 2012 in more than 500 individuals cases, the United Nations Human Rights Committee concluded that South Korea violated article 18 of International Covenant on Civil and Political Rights (ICCPR) which guarantees freedon of conscience. In 2014, the committee adopted it’s 5th view against South Korea. The Committee accepted the authors claim that Souht Korea also violated Article 9 of the Covenant which prohibits arbitrary detention. On December 12th 2012, The Universal Periodic Review by United Nations Human Rights Council aims to assess the Human Rights situation in all it’s United Nations member states.The delegates of 8 state parties strongly urged South Korea to introduced an alternative service. But Korean Government has not taken any measures to improve human rights despite international warning.According to the current situation, Korean Government has to take the neccesary steps for recognizing Conscientious Objection by introducing the alternative service system.